The Intermediate Filament Architecture as Determined by X-Ray Diffraction Modeling of Hard α-Keratin - Er Rafik, Mériem; Doucet, Jean; Briki, Fatma (Biophysical journal, 2004)
Despite investigation since the 1950s, the molecular architecture of intermediate filaments has not yet been fully elucidated. Reliable information about the longitudinal organization of the molecules within the filaments and about the lateral interfilament packing is now available, which is not the case for the transverse architecture. Interesting results were recently obtained from in vitro microscopy observations and cross-linking of keratin, desmin, and vimentin analyses. The structural features that emerge from these analyses could not be fully representative of the in vivo architecture because intermediate filaments are subject to polymorphism. To bring new light to the transverse intermediate filament architecture, we have analyzed the x-ray scattering equatorial profile of human hair. Its comparison with simulated profiles from atomic models of a real sequence has allowed results to be obtained that are representative of hard α-keratin intermediate filaments under in vivo conditions. In short, the α-helical coiled coils, which are characteristic of the central rod of intermediate filament dimers, are straight and not supercoiled into oligomers; the radial density across the intermediate filament section is fairly uniform; the coiled coils are probably assembled into tetrameric oligomers, and finally the oligomer positions and orientations are not regularly ordered. These features are discussed in terms of filament self-assembling and structural variability.